2017
DOI: 10.1038/srep45128
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase SOD-1 modulates C. elegans pathogen avoidance behavior

Abstract: The C. elegans nervous system mediates protective physiological and behavioral responses amid infection. However, it remains largely unknown how the nervous system responds to reactive oxygen species (ROS) activated by pathogenic microbes during infection. Here, we show superoxide dismutase-1 (SOD-1), an enzyme that converts superoxide into less toxic hydrogen peroxide and oxygen, functions in the gustatory neuron ASER to mediate C. elegans pathogen avoidance response. When C. elegans first encounters pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…A number of sensory neurons required for pathogen avoidance have been identified [ 6 , 11 , 19 , 34 ]. In some cases, these neurons appear to regulate the avoidance of more than one pathogen; for example AWB is required for the avoidance of both S. marcescens and P. aeruginosa [ 6 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of sensory neurons required for pathogen avoidance have been identified [ 6 , 11 , 19 , 34 ]. In some cases, these neurons appear to regulate the avoidance of more than one pathogen; for example AWB is required for the avoidance of both S. marcescens and P. aeruginosa [ 6 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“… Horspool and Chang (2017) show that sod-1 expression is specifically induced in the gustatory neuron ASER in response to pathogenic bacteria and that this up-regulation is required to mediate pathogen avoidance. Horspool and Chang (2017) interpret these findings to suggest that pathogen-induced ROS activate a sod-1 –dependent pathway to mediate the avoidance behavior. SODs have also been shown to be required in a developmental context: the development of the vulva, which is regulated by the RAS signaling pathway.…”
Section: The Biology Of Sod In Model Animalsmentioning
confidence: 86%
“…There is also a very interesting study on cell-specific up-regulation of sod-1 ( Horspool and Chang, 2017 ). Horspool and Chang (2017) show that sod-1 expression is specifically induced in the gustatory neuron ASER in response to pathogenic bacteria and that this up-regulation is required to mediate pathogen avoidance.…”
Section: The Biology Of Sod In Model Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reveal that pathogenic bacteria Pseudomonas aeruginosa , which are frequently found in the habitats of nematodes [15] , [16] , can colonize the intestine of C. elegans [17] , [18] , [19] , [20] . Switching C. elegans from a diet of E. coli to a diet of P. aeruginosa creates a condition that mimics gut dysbiosis [21] , [22] , [23] . The change in the microbial composition in the intestine activates host responses [22] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%